2020
DOI: 10.1186/s12984-020-00750-x
|View full text |Cite
|
Sign up to set email alerts
|

Exoskeleton use in post-stroke gait rehabilitation: a qualitative study of the perspectives of persons post-stroke and physiotherapists

Abstract: Background Wearable powered exoskeletons are a new and emerging technology developed to provide sensory-guided motorized lower limb assistance enabling intensive task specific locomotor training utilizing typical lower limb movement patterns for persons with gait impairments. To ensure that devices meet end-user needs it is important to understand and incorporate end-users perspectives, however research in this area is extremely limited in the post-stroke population. The purpose of this study was to explore in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 57 publications
3
77
0
Order By: Relevance
“…In stroke, comparative qualitative data relating to RAGT are limited and con icting. A study by Vaughan-Graham et al (2020) reported that chronic stroke survivors while hopeful about exoskeleton technology, expressed disappointment that the technology did not yet meet their expectations (22). In contrast a recent study conducted in a subacute stroke population reported positive perceptions of exoskeleton-based physiotherapy which better echoing the ndings in this study, where patients rated it favourably, attributing opportunity and bene t to using the device during subacute rehabilitation (23).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In stroke, comparative qualitative data relating to RAGT are limited and con icting. A study by Vaughan-Graham et al (2020) reported that chronic stroke survivors while hopeful about exoskeleton technology, expressed disappointment that the technology did not yet meet their expectations (22). In contrast a recent study conducted in a subacute stroke population reported positive perceptions of exoskeleton-based physiotherapy which better echoing the ndings in this study, where patients rated it favourably, attributing opportunity and bene t to using the device during subacute rehabilitation (23).…”
Section: Discussionsupporting
confidence: 62%
“…The amount of time required to record individual anthropometric measurements and t the device were identi ed as negative aspects. This limitation was mirrored in other qualitative studies examining device users' (21,22,23) and therapists' perspectives (23,29,30,31) of RAGT. However, this current study recorded only early perceptions following each participant's rst two trials of using the device where the burden of assessment and setup has previously been reported as highest (30).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moderate correlations were observed between question 5 and physiotherapists’ age and years of experience in the neurorehabilitation field and with MS. The ability to adjust the exoskeleton to the patients’ needs such as the amount of assistance provided to optimize patients’ gait pattern is an essential skill for the physiotherapists [ 47 ]. The high score and the obtained correlation seem to indicate that EKSO GT ® could properly adapt to patients’ and physiotherapists’ needs.…”
Section: Discussionmentioning
confidence: 99%
“…Exoskeletons are physical human-robot interfaces (HRIs) conceived for several purposes such as rehabilitation, assistance, and haptic interaction in virtual or remote environments (Pons, 2008 ). The robotic community put a strong effort into developing wearable powered robots since at least 1967 (Mosher, 1967 ) when one of the earliest exoskeleton for motion augmentation was presented.…”
Section: Introductionmentioning
confidence: 99%